2008
DOI: 10.3171/ped.2008.2.10.254
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of developmental outcome in patients with cephaloceles

Abstract: Object Cephaloceles represent primary axial mesodermal defects, occurring in 0.8–4 per 10,000 live births. Prior studies have reported posterior location, hydrocephalus, microcephaly, seizure, and presence of brain tissue as poor prognostic markers for neurological outcome. However, these studies were small and the results were analyzed using univariate tests. The purpose of this study was to investigate the potential risk factors for the occurrence of developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
104
2
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 7 publications
5
104
2
7
Order By: Relevance
“…Our review has confirmed previous findings that hydrocephalus is significantly associated with cognitive deficit in patients with encephaloceles. 8,9,19 While patients with posterior encephaloceles had a higher rate of progressive hydrocephalus (15/56) and developmental delay (35/56) than those with anterior lesions (2/14 and 7/14, respectively), there was no statistically significant difference between these rates, confirming the finding by Lo et al 19 A sample of large reviews is shown in Table 5 for comparison with our results.…”
Section: Discussionsupporting
confidence: 80%
“…Our review has confirmed previous findings that hydrocephalus is significantly associated with cognitive deficit in patients with encephaloceles. 8,9,19 While patients with posterior encephaloceles had a higher rate of progressive hydrocephalus (15/56) and developmental delay (35/56) than those with anterior lesions (2/14 and 7/14, respectively), there was no statistically significant difference between these rates, confirming the finding by Lo et al 19 A sample of large reviews is shown in Table 5 for comparison with our results.…”
Section: Discussionsupporting
confidence: 80%
“…Severe microcephalus was seen in 3 infants, which was accompanied by a poor prognosis, compatible with previous reports [16,40]. Naidich et al [21] have proposed that a lack of associated microcephaly, holoprosencephaly, or ventriculomegaly is a criterion for a good long-term prognosis in cephalocele-affected children.…”
Section: Discussionsupporting
confidence: 74%
“…A birth survey in Bangkok reported an incidence of 1 in 6,000 [15]. Lo et al [16] reported 40 frontal lesions out of 85 cephaloceles in one of the largest series in North America, contrasting previous reports. This fact may be a consequence of ethnic changes, due to an increasing rate of people immigrating to Canada during the past few years.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…The prognosis for patients with a cephalocele depends primarily on site, content of the sac, operability, hydrocephalus, and additional malformations [16,25,29,30,31,34,36,48,53].…”
Section: Discussionmentioning
confidence: 99%